Factors influencing the agreement between teachers and students in the assessment of preclinical endodontics using a rubric - B. Baracco; N. Escribano; D. Da Silva; V. Belliard; L. Ceballos; V. Fuentes (BMC Medical Education)
Abstract Background Students’ self-assessment and rubrics are pedagogical tools designed to enhance learning and evaluation processes. Achieving convergence between learners and teachers is paramount during the learning of complex treatments such as endodontic procedures, although it can be challenging due to uncontrollable factors that may affect task performance and perception. This study aimed to evaluate the influence of various factors (anatomical difficulty, type of instrumentation system, and training level) on the assessments of root canal treatments (RCT) by teachers and students using a rubric, and to determine the degree of agreement between them. Methods 144 RCT were performed on extracted human molars by 36 dental students using two mechanized systems and subsequently evaluated using a rubric by both the students and four teachers. Rubric yielded a total score for the sum of 4 items analyzed individually: radiographic evaluation, access cavity, instrumentation, and obturation. The influence of the three following factors: anatomical difficulty (categories: minimal, moderate and high), instrumentation system (categories: Protaper Next and Reciproc Blue), and training level (categories: initial and advanced) on teachers’ and students’ RCT total scores and for each item were analyzed by three-way ANOVA. Agreements between teachers and students were measured by intraclass correlation coefficients and quadratic weighted Kappa. Statistical analyses were conducted at a pre-set alpha of 0.05 using Stata 16. Results No significant influence of anatomical difficulty, instrumentation system, or training level was observed on RCT total scores given by teachers and students (p > 0.05). However, training level influenced the assessments by teachers in instrumentation as those by students in radiographic evaluation. Agreement was moderate for RCT total scores and substantial for teeth with minimal or high difficulty, after using Protaper Next, and at the initial training level. Agreement was substantial in obturation, and moderate in radiographic evaluation, access cavity, and instrumentation. Some categories in instrumentation and obturation items showed substantial agreement, while fair agreement was observed only in access cavity. Conclusions Educational factors in Endodontics such as anatomical difficulty, mechanized instrumentation system, and level of training did not influence the total scores of preclinical RCT by teachers or students. Agreement for RCT total scores ranged from moderate to substantial. The strongest agreement was observed in obturation, while access cavity yielded the lowest. The rubric as an assessment tool in Endodontics teaching is recommended.